Analisis Keselamatan dan Kesehatan Kerja (K3) Menggunakan Metode Job Safety Analysis (JSA) dan Hazard and Operability Study (HAZOPS) pada Departemen SDM PT. Micro Madani Institute Cabang Solo - Gessa Sevic Avrilliano; Erna Indriastiningsih; Anita Oktaviana Trisna Devi (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Occupational Safety and Health (K3) is an important aspect in protecting workers from potential accidents and health problems arising from work activities, including in the administrative sector, which is often considered low-risk. However, the Human Resources (HR) Department at PT Micro Madani Institute (MMI) Solo Branch still found several potential hazards and work risks that have not been optimally identified. This study aims to apply the Hazard and Operability Study (HAZOPS) and Job Safety Analysis (JSA) methods to identify and mitigate hazards and work accident risks in the HR Department's activities at PT Micro Madani Institute (MMI) Solo Branch. The research method is a qualitative study with a descriptive approach through observation and interviews. Risk analysis used the JSA and HAZOPS methods. The results of the study show that the application of the HAZOPS method in five sections of the HR Department successfully identified 53 potential hazards and risks, consisting of 12 extreme risks, 23 high risks, 15 moderate risks, and 3 low risks with the Employee Training and Development section as the section with the largest number of risks. Meanwhile, the application of the JSA method also identified 53 potential hazards and risks from 19 work activities. The dominant risks stem from non-ergonomic work postures, prolonged sitting, intensive computer use, and high workloads. This study concludes that the JSA and HAZOPS methods are effective in identifying potential occupational hazards and risks and can serve as the basis for control efforts to minimize workplace accidents and improve OHS implementation in the HR Department.